De-addiction through the Lens of Learning Theories: Insights from an Ayurvedic Perspective - Mishra, Rishabh; Prakash Singh, Jai; Antiwal, Meera (International Research Journal of Ayurveda & Yoga, 2025)
De-addiction is a multifaceted process requiring a blend of biological, psychological, and social interventions. While Ayurveda emphasizes holistic healing through body-mind balance, learning theories offer valuable insights into the behavioral and cognitive mechanisms underpinning addiction and recovery. This article explores the application of prominent psychological and sociological learning theories, such as Albert Bandura’s Social Learning Theory, B.F. Skinner’s Operant Conditioning, and others, in understanding and addressing addiction within the framework of Ayurveda.